UTILIZATION OF RAINWATER TO REDUCE WATER RUNOFF DISCHARGE IN THE KELAPA GADING PUMP BUILDING AREA USING THE SUNJOTO METHOD - Mohammad Imamuddin; Basit Al Hanif; Afinda Deja Yuliansyah (International Journal of Civil Engineering and Infrastructure, 2023)
Increased development of community facilities triggers changes in land use that result in less open land for infiltration. This causes run-off and little rainwater is absorbed by the soil. For this reason, it is necessary to make a reservoir in the form of an infiltration well that functions to accommodate and absorb rainwater into the ground slowly. The purpose of this study was to determine the number and point of infiltration wells. The research was conducted at the Kelapa Gading Pumping Building located in North Jakarta. The address of the registered entity is Jl. Gading Mas Timur I No. 17, RT.12 / RW.10, Pegangsaan Dua Village, Kelapa Gading District, North Jakarta City, where the Kelapa Gading Pump Building stands on an area of ± 4,000 m2, has a reservoir with an area of ± 1,955 m2 with supporting buildings in the form: 1. pump building of 160 m2, 2. substation house of 35 m2, 3. transformer house of 75 m2, 4. employee mess of 52 m2, 5. generator house of 75 m2. This research uses survey methods in the form of measurements, interviews, and to obtain the required data. Based on the data and calculation analysis according to SNI 846-2017, a circular infiltration well with a diameter of 1meter and a depth of 2 meters to 2.5 meters can be determined.